Beyond Legislative Veto Power: The Transformative Effects of the Early Warning System for Subsidiarity Control Ten Years Down the Line - Borońska-Hryniewiecka, Karolina (Política y Sociedad, 2021)
The majority of European Union (EU) studies tend to be critical of the Early Warning System (EWS) for subsidiarity control, deeming it as ineffective in blocking unwanted EU legislation. Against this background, the aim of this paper is to identify and discuss several transformative effects of the EWS connected with the quality and democratic character of the EU governance, beyond the tool’s legislative veto power. A critical review of the EWS’ interpretations as an accountability mechanism, Europeanization engine, parliamentary autonomy enhancing tool, platform of politicization of Europe, as well as an instrument improving the Commission’s regulatory culture reveals that —although flawed by design— the modus operandi of the EWS has in fact contributed to reinforcing the input legitimacy of the EU. The argument is also made that the EWS should be viewed as a sort of ‘reality-check’ for the EU’s legislative moderation, thus enhancing the ‘perceived output legitimacy’ of the EU policy-making. The paper, however, concludes that although the positive effects of the EWS ought to be recognized and valued, the mechanism in its current form has exhausted its democratic potential and needs to be complemented with new forms of representative politics in EU affairs.